The Effect of Different Physiotherapy Programs on Pain, Balance and Trunk Functional Capacity in Adolescents with Low Back Pain - Lina Budrienė; Gabrielė Gudaitė (Lithuanian Sports University, 2022)
Background. Low back pain is a common problem, adversely affecting balance and strategy for controlling the trunk muscles. There are various methods to treat low back pain, therefore, studies comparing the effectiveness of different programs can help improve the rehabilitation program for patients with low back pain. The aim. To evaluate the effect of trunk stabilization and balance exercises performed with different devices on pain, balance and trunk functional capacity in adolescents with low back pain. Methods. 12 adolescents with low back pain participated in this study. They were divided into two groups. The first group received 20 minutes of stabilization exercises and 10 minutes of balance training using the Biodex balance system. The second group received 20 minutes of stabilization exercises and 10 minutes of balance training using a vibration platform. All subjects were evaluated before and after 10 physiotherapy procedures. Self-reported pain, balance and static endurance of trunk muscles were assessed before and after the interventions. Results. Both programs significantly reduced pain, improved control of the center of gravity within the base of support, reduced the time required to shift weight in different paths, reduced sway index in conditions of eyes open or eyes closed on a firm or foam surface, improved dynamic and static overall postural stability and increased static endurance of trunk muscles. Improvement in control of the center of gravity within the base of support, and reduction in the time required to shift weight in different paths, were more significant in the group that received balance training using the Biodex balance system compared with that in the group that received balance training using a vibration platform. Conclusions. Balance training using the Biodex balance system was more effective in improving control of the center of gravity within the base of support and reducing the time required to shift weight in different paths than balance training using a vibration platform. Keywords: low back pain, balance, trunk stability, Biodex balance system, vibration platform.